Analisis Yuridis Penetapan Status Tersangka Ditinjau dari Perspektif Hak Asasi Manusia - Solina Sances; Eko Nurisman (Journal of Judicial Review, 2016)
The problem of law enforcement in Indonesia require legal form, its about right of suspect raises many disagreement by the legal expert, In principle criminal law (KUHAP) adopted principle equality and presumption of innocence until got the judge’s decision. Based on the research , the researcher got two formulation of the problem, first legal certaintly regarding the deadline of determination of suspect reviewed from human right perspective, second the implementation presumption of innocence human right perception. Purpose of the research for analyze juridical on how legal certainty about limitation of suspect and implementation principle presumption of innocent reviewed from human right perspective. The Stuy used normative juridical research method. Data source is secondary data which obtained from the literature. The data processed andanalysed using qualitative. Classifying the aspect studied and got the conclusion related to this research. The data described descriptively. Based on this research, the result reviewed by researcher into conclusions, its about legal certainty of limits determination of the suspect not related to human right perpective, implementation presumption of innoncence by law enforcer wasnt prioritize human right. Based on this study, the obtained results have been reviewed by researchers that the conclusion that the legal certainty regarding the deadline for determination of the suspect is not in accordance with the human rights perspective, the application of the presumption of innocence by law enforcement is not in accordance with the human rights perspective, because there are no rules regulating exactly how the application of the principle of presumption of innocence so that their legal vacuum.